Role of Apis cerana cerana N-terminal asparagine amidohydrolase (AccNtan1) in oxidative stress. (2nd July 2020) - Zhao, Guangdong; Wang, Chen; Wang, Ying; Wang, Lijun; Xu, Baohua; Guo, Xingqi
Abstract: N-Terminal asparagine amidohydrolase is a component of the ubiquitin-dependent N-end rule pathway of protein degradation that has been implicated in a variety of physiological functions, including the sensing of heme, oxygen, nitric oxide, selective elimination of misfolded proteins and the repair of DNA. We identified the Apis cerana cerana N-terminal asparagine amidohydrolase ( AccNtan1 ) gene from A. cerana cerana and investigated its role in oxidation resistance. Multiple sequence alignments and phylogenetic analysis revealed that N-terminal asparagine amidohydrolase is highly conserved in insect species. Quantitative real-time polymerase chain reaction analysis indicated that the expression levels of AccNtan1 were significantly lower in the wing, honey sac and abdomen than in other tissues and were significantly higher in early stages of development, including the larva, prepupa and pink-eyed pupa stages, than in later stages. We further observed that AccNtan1 expression was induced by several environmental stressors, including aberrant temperature, H2 O2, UV, heavy metals and pesticides. Moreover, a bacteriostatic assay suggested that overexpression of AccNtan1 enhances the resistance of bacteria to oxidative stress. In addition, knockdown of AccNtan1 using RNA interference significantly affected the expression levels of most antioxidant genes and the activity levels of several antioxidant enzymes. Thus, we hypothesize that AccNtan1 plays important roles in environmental stress responses and antioxidative processes.